Togo – 2019 : Domestic politics, foreign affairs, socio-economic development - Kohnert, Dirk (My University, 2020)
ABSTRACT: Controversial constitutional and institutional reforms voted in May in parliament opened the way for President Gnassingbé to stand for a fourth and fifth term (2020 and 2030) because the law does not apply retroactively. The first local elections since more than 30 years resulted in the victory of the ruling party. Grand expectations of the opposition which had hoped for a fundamental change at least at the grassroots were again dashed. The human rights situation sharply deteriorated due to growing political and social tensions related to the prospects of the head of state running for a fourth term. Islamist terrorist violence spread from Mali to the northern frontier region of Togo. The autonomous deep-water port of Lomé developed as a growth pole and hub for the sub-region. China became the major partner beside the established partners the EU, France and Germany. The informal sector still dominated the economy. Economic freedom remained with the overall status 'mostly unfree'. RÉSUMÉ: Des réformes constitutionnelles et institutionnelles controversées votées en mai au Parlement ont ouvert la voie au président Gnassingbé pour se présenter aux quatrième et cinquième mandats (2020 et 2030) car la loi ne s'applique pas rétroactivement. Les premières élections locales depuis plus de 30 ans ont abouti à la victoire du parti au pouvoir. Les grandes attentes de l'opposition qui avait espéré un changement fondamental au moins à la base ont de nouveau été déçues. La situation des droits de l'homme s'est fortement détériorée en raison des tensions politiques et sociales croissantes, liées aux perspectives d'un quatrième mandat du chef de l'État. La violence terroriste islamiste s'est propagée du Mali à la région frontalière nord du Togo. Le port autonome en eau profonde de Lomé s'est développé comme un pôle de croissance et un hub pour la sous-région. La Chine est devenue le principal partenaire aux côtés des partenaires établis, l'UE, la France et l'Allemagne. Le secteur informel dominait toujours l'économie. La liberté économique est restée avec le statut global «pour la plupart non libre».
Keywords: African Affairs; African Studies; ECOWAS; Togo; UEMOA; WAEMU; West Africa